Nanoporous Materials: Beating Thermal Coarsening in Nanoporous Materials via High‐Entropy Design (Adv. Mater. 6/2020). Issue 6 (11th February 2020) - Joo, Soo‐Hyun; Bae, Jae Wung; Park, Won‐Young; Shimada, Yusuke; Wada, Takeshi; Kim, Hyoung Seop; Takeuchi, Akira; Konno, Toyohiko J.; Kato, Hidemi; Okulov, Ilya V.
Abstract : In article number 1906160, Soo‐Hyun Joo, Hidemi Kato, and co‐workers pioneer a novel high‐entropy design strategy for the synthesis of nanoporous materials with exceptional thermal stability at elevated temperatures. Multiprincipal element alloying overcomes the universal relationship of coarsening via suppressed surface diffusion, and the preservation of size‐related physical properties is the key benefit of high‐entropy design.